Remarks on the diachronic reconstruction of intonational patterns in Romance with special attention to Occitan as a bridge language - José Ignacio Hualde (Universitat Autònoma de Barcelona, 2003)
This paper approaches Romance intonation from a diachronic point of view. The position that is adopted is that this is an area open to investigation. Comparative techniques can be fruitfully employed for investigating the evolution and diversification of the intonational patterns of the Romance languages. The focus of the paper is on Occitan. This is an important bridge language whose study may elucidate how French diverged prosodically from the systems found in Ibero and Italo-Romance. It is argued that, since Occitan was retained contrasts in the position of wordaccent (lexical stress), any prosodic features that French shares with Occitan are logically independent from the lack of contrastive accent in French.